Standalone photovoltaic systems sizing optimization using design space approach: Case study for residential lighting load - Al Riza, D.F. (Taylor's University, 2015)
This paper presents a sizing optimization methodology of panel and battery capacity in a standalone photovoltaic system with lighting load. Performance of the system is identified by performing Loss of Power Supply Probability (LPSP) calculation. Input data used for the calculation is the daily weather data and system components parameters. Capital Cost and Life Cycle Cost (LCC) is calculated as optimization parameters. Design space for optimum system configuration is identified based on a given LPSP value, Capital Cost and Life Cycle Cost. Excess energy value is used as an over-design indicator in the design space. An economic analysis, including cost of the energy and payback period, for selected configurations are also studied. Â© 2015, School of Engineering, Taylorâs University.